Left-Right Model of Electroweak Interaction with One Bidoublet and One Doublet Higgs Fields - Asan Damanik (Indonesian Journal of Physics, 2010)
We study the predictions of the left-right model of electroweak interaction based on SU(2)L ⊗ SU(2)R ⊗ U(1) gauge group by using one bidoublet and one doublet Higgs fields. By choosing appropriate vacuum expectation values of Higgs fields, the low energy phenomenology of electroweak interaction can be understood. Leptons can acquire a mass via two scenarios, first via a Higgs mechanism with non-zero 'hypercharge-like' I in the Lagrangian density mass terms with the Yukawa couplings G1 >> G1* , and the second via a Higgs mechanism followed by a seesaw-like mechanism without the requirement that G1 >> G1*